Interfacing PIC Microcontrollers to Peripherial Devices - Borowik, Bohdan (Intelligent Systems, Control and Automation: Science and Engineering,, 2011)
This book is targeted for students of electronics and computer sciences. The first part of the book contains 15 original applications working on the PIC microcontroller, including: lighting diodes, communication with RS232 (bit-banging), interfacing to 7-segment and LCD displays, interfacing to matrix keypad 3 x 4, working with PWM module and others. This material can be used to cover one semester's teaching of microcontroller programming or similar classes. The volume contains schematic diagrams and source codes with detailed descriptions. All tests were prepared on the basis of the original documentation (data sheets, application notes). The next three chapters: The Stack, Tables and Table Instruction and Data Memory pertain to PIC18F1320. Software referred to is also presented in assembly language. Finally the application of the PIC24FJ microcontroller with the 240x128 LCD display, T6963C and with accelerometer sensor, written in C are described.